STRATEGI KESANTUNAN YANG TERCERMIN DALAM MODEL PERCAKAPAN PADA BUKU BAHASA INGGRIS KELAS 6 SD - Liliek Soepriatmadji (Dinamika Bahasa dan Budaya, 2012)
The study is aimed at describing the politeness strategies, explaining the degree of directness, and FTA potential of the utterances adopted in the model conversations of English textbooks for sixth graders in Semarang. The findings indicate that (1) the model conversations display doing no FTA, FTA off Record, Neg FTA Bald on Record and Pos FTA Bald on Record as the politenesss strategies with doing no FTA as the dominant strategy. (2) The utterances in the model conversations tend to be direct. (3) Some utterances contain FTA potentials. In order to justify whether the conversations are appropriate or not, a further study needs to be conducted with respect to the organization of conversation, thus genre or coherency, turn taking organization, and other variables such as the social status of the participants, gender, time force, circumstances, etc. Key words: politeness strategy, FTA, model conversation.